A Review of Certification Compliance Assessment for Nonresettable Protection Devices in eVTOL Applications - Shadan Altouq; Chung M. Fong; Patrick J. Norman; Graeme M. Burt (IET Electrical Systems in Transportation)
The introduction of electrical vertical take-off and landing (eVTOL) aircraft enables a greener, quieter, and faster method of aerial transportation method than helicopters. Key electrical power technologies are also being developed to enable the realization of these new aircraft types. The Pyrofuse protection device is a nonresettable protection device (NRPD) that offers desirable features for use within small electric aircraft applications. The components used in the Pyrofuse are also currently available at the intended power levels and at low cost. However, the nonresettable aspect of the device represents a challenge in the certification process for its use in eVTOL electrical system protection, although there is a current shortage of published literature on this aspect. Accordingly, this paper provides the first document-based review of certification compliance assessment for the use of NRPDs in an eVTOL environment. This assessment shows that devices such as Pyrofuses can achieve airworthiness in a range of roles as the primary protection for eVTOL electrical power system (EPS). However, this airworthiness is highly dependent on the physical design of the aircraft design, the proposed location of NRPDs, and the immunity to common mode and common cause failures.